Multi-omics reveals the mechanism of quality discrepancy between Gayal (Bos frontalis) and yellow cattle beef - Lin Han; Runqi Fu; Chunjia Jin; Huan Gao; Binlong Fu; Qian Li; Ye Yu; Min Qi; Jiawei Zhang; Shengyong Mao; Jing Leng (BMC Genomics)
Abstract Background Producing high-quality beef with enhanced muscle composition and reduced fat content is critical for meeting consumer preferences and supporting a balanced diet. Given the substantial variability in beef quality across cattle breeds, this study aimed to identify key determinants of meat quality by examining Gayal (Bos frontalis) and yellow cattle (Bos taurus) through a multi-disciplinary approach. Results The results demonstrated that Gayal cattle exhibited superior meat quality, characterized by higher levels of protein, flavor-enhancing and essential amino acids, total amino acids, and polyunsaturated fatty acids (PUFAs), alongside reduced fat content, with similar trends observed in serum hormone and amino acid profiles. Distinct differences in gut microbial composition, enzymatic activities, and metabolites were observed between the breeds. Gayal displayed increased abundances of key bacterial taxa such as Akkermansia, Paeniclostridium, Escherichia-Shigella, and Clostridium sensu stricto 1, which were associated with enhanced volatile fatty acids (VFAs), ammoniacal nitrogen, and enzymatic activity in the colon. Transcriptomic analysis of the psoas major (PM) muscle revealed significant changes in genes linked to muscle development, amino acid metabolism, and lipid metabolism. Genes related to intestinal amino acid absorption were upregulated in Gayal, while those connected to short-chain fatty acid absorption were downregulated. Correlation analyses underscored the role of gut microbiota and metabolic profiles in modulating gene expression associated with lipid and amino acid metabolism, ultimately influencing meat flavor and quality. Conclusions These findings provide actionable insights into the genetic and microbial factors underlying beef quality, offering a foundation for enhancing local cattle resources, optimizing breeding programs, and advancing the production of premium beef to meet both market and dietary needs.